Is it stress? The role of stress related systems in chronic food restriction-induced augmentation of heroin seeking in the rat - Sedki, Firas; Abbas, Zarish; Angelis, Staci; Martin, Jeffrey; D'Cunha, Tracey; Shalev, Uri (Frontiers in Neuroscience, 2013)
Drug addiction is a chronic disease characterized by recurring episodes of abstinence and relapse. The precise mechanisms underlying this pattern are yet to be elucidated, but stress is thought to be a major factor in relapse. Recently, we reported that rats under withdrawal and exposed to a mild chronic stressor, prolonged food restriction, show increased heroin seeking compared to sated controls. Previous studies demonstrated a critical role for corticotropin-releasing factor (CRF) and corticosterone, hormones involved in the stress response, in acute food deprivation-induced reinstatement of extinguished drug seeking. However, the role of CRF and corticosterone in chronic food restriction-induced augmentation of drug seeking remains unknown. Here, male Long-Evans rats were trained to self-administer heroin for 10 days in operant conditioning chambers. Rats were then removed from the training chambers, and subjected to 14 days of unrestricted (sated rats) or a mildly restricted (FDR rats) access to food, which maintained their body weight at 90% of their baseline weight. On day 14, different groups of rats were administered a selective CRF1 receptor antagonist (R121919; 0.0, 20.0 mg/kg; s.c.), a non-selective CRF receptor antagonist (α-helical CRF; 0.0, 10.0, 25.0 μg/μl; i.c.v.) or a glucocorticoid receptor antagonist (RU486; 0.0, 30.0 mg/kg; i.p.), and underwent a 1 h drug seeking test under extinction conditions. An additional group of rats was tested following adrenalectomy. All FDR rats showed a statistically significant increase in heroin seeking compared to the sated rats. No statistically significant effects for treatment with α-helical CRF, R121919, RU486 or adrenalectomy were observed. These findings suggest that stress may not be a critical factor in the augmentation of heroin seeking in food-restricted rats.